(untitled) (MAUSAM, 2004)
Although, monsoon rainfall (June-September) over the country as a whole has shown some resilience for variations, it has shown remarkable variations over smaller regions viz. over the Northwestern parts of the country. This study is an attempt to predict seasonal rainfall departure over the Northwest India with the help of an “area averaged OLR anomaly index” associated with the North Atlantic Oscillation (NAO) over parts of North Atlantic Ocean during May. Using the OLR anomaly index developed in this study for the period 1979-2000, a simple regression equation was developed and the performance of the model was evaluated through the “Cross validation” technique. The Root Mean Square (RMS) error of the model (9.73) was much less than the standard deviation (17.51) of the rainfall over NW India, indicating the skill of the model.